Exploring the concept of cross-dressing in Shakespeare's plays: uncovering the SHE - Shahid, Tasnim (BRAC University, 2014)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2013.